Development and characterization of microsatellite loci for Ficus hirta (Moraceae)1. (14th July 2015) - Zheng, Linna; Nason, John D.; Liang, Dan; Ge, Xuejun; Yu, Hui
Abstract : Premise of the study: Microsatellite primers were developed to investigate population genetic structure in Ficus hirta (Moraceae). Methods and Results: Sixteen microsatellite primers were developed and optimized for F. hirta using Illumina paired‐end sequencing of pre‐receptive and receptive developmental‐phase female flowers. Out of 16 primers, nine were found to be polymorphic in four populations of F. hirta . Alleles per locus ranged from two to 15 across the 94 F. hirta individuals, while within‐population observed and expected heterozygosity per locus ranged from 0.000 to 0.955 and from 0.000 to 0.882, respectively. In addition, the 16 primers were tested in 29 additional Ficus species, with all found to amplify in at least 11 of these species and with most amplifying in a majority of the species. Conclusions: This set of microsatellite primers is the first specifically developed for F. hirta and will facilitate studies of genetic diversity within and genetic differentiation among populations of Ficus species.